Exploring suspended sediment delivery dynamics of two Mediterranean nested catchments. Issue 3 (28th November 2016) - López‐Tarazón, José A.; Estrany, Joan
Abstract: This paper investigates suspended sediment transport and dynamics of two nested agricultural lowland Mediterranean catchments with a difference of two orders of magnitude in the surface area (i.e., 1 and 264 km 2 ). The effects of the drainage catchment area over the specific suspended sediment yield are assessed by using the nested approach over various timeframes. A detailed analysis of the rainfall–runoff–sediment transport relationships during the 2‐year study period shows that the hydrological and sedimentological responses were extremely variable for both catchments. Very low or no correlations were observed between the rainfall intensity and the selected hydrological variables and sediment loads. However, remarkable or high correlations were obtained between the rainfall intensity and the maximum and average suspended sediment concentrations, indicating that rainfall per unit time has little control on the hydrological response, but that, simultaneously, its high‐erosive power triggers sediment production, increasing the sedimentary response of the catchments. This study also illustrates how sediment is mainly transported during floods, producing predominantly clockwise hysteretic loops. Moreover, the small headwater catchment exerts a reduced (or even negligible) effect over the hydro‐sedimentary response of the larger downstream catchment, caused by the reduced sediment availability in a landscape with an inherent disconnection of the sediment pathways.